The Impact of Authentic Leadership on The Work Motivation of Generation Z Employees in Indonesia - Abdullah Haidar; Maura Najwa Maitsa (Publication of the International Journal and Academic Research, 2026)
The increasing participation of Generation Z in Indonesia’s workforce has created new challenges for organizations, particularly in maintaining employee motivation, engagement, and long-term retention. Compared with previous generations, Generation Z places stronger emphasis on transparency, meaningful work, and trust-based relationships with leaders. Although previous studies have extensively discussed leadership style and turnover intention, limited empirical research has specifically examined how authentic leadership influences work motivation among Generation Z employees in the Indonesian context. Since work motivation functions as a psychological foundation for employee engagement, commitment, and retention, examining this relationship is considered important both theoretically and practically. Therefore, this study aims to analyse the impact of authentic leadership on the work motivation of Generation Z employees in Indonesia. This study employed a quantitative survey design involving 361 Generation Z employees from five major provinces in Indonesia selected through purposive sampling. Data were collected through a structured online questionnaire and analysed using validity, reliability, and simple linear regression tests. Validity testing confirmed that all measurement items were statistically valid, while reliability testing demonstrated strong internal consistency, with Cronbach’s Alpha values of 0.916 and 0.981 for Authentic Leadership and Work Motivation, respectively. The results showed that authentic leadership has a positive and statistically significant effect on work motivation (β = 0.734; p < 0.001), with an R² value of 0.653, indicating that authentic leadership explains 65.3% of the variance in work motivation. These findings confirm that authentic leadership plays an important role in strengthening the motivation of Generation Z employees in Indonesia. Practically, organizations are encouraged to implement leadership development initiatives focused on self-awareness, transparent communication, ethical decision-making, and regular feedback practices to improve employee motivation, engagement, and long-term retention among Generation Z in the workplace.